2016
DOI: 10.1002/dc.23510
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast mucormycosis: FNAC diagnosis of a rare entity

Abstract: Mucormycosis is the common name given to several different diseases caused by fungi in the order of mucorales. The clinical hallmark of these opportunistic pathogens in invasive mucormycosis is tissue necrosis resulting from angioinvasion and subsequent thrombosis. Rarely the disease may affect immunocompetent individuals. In addition, the breast involvement in this disease is very rare. Herein, we describe a case of primary breast mucormycosis diagnosed on fine needle aspiration cytology (FNAC), in an immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…15 The average duration of symptoms before diagnosis is highly variable, spanning from a few weeks in Europe to more than 7 months in India and sub-Saharan Africa. 1,3,11,21,22 This includes both patient and health system delays, and reflects the range of cultural, psychological, and economic components, as well as the diagnostic challenges. The disease is generally mono-lateral and can equally affect either breast as in case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The average duration of symptoms before diagnosis is highly variable, spanning from a few weeks in Europe to more than 7 months in India and sub-Saharan Africa. 1,3,11,21,22 This includes both patient and health system delays, and reflects the range of cultural, psychological, and economic components, as well as the diagnostic challenges. The disease is generally mono-lateral and can equally affect either breast as in case.…”
Section: Discussionmentioning
confidence: 99%
“…4,[24][25][26] We could also added other infectious diseases, such as brucellosis, actinomycosis, mycotic infections, and fat necrosis. 22,25 Using PCR or culture as standards by default, no test has satisfactory sensitivity and limited specificity. Of the M. tuberculosis detection methods, microscopy with AFB has, probably, the best balance between sensitivity (∼80%) and specificity (35%-65%).…”
Section: Discussionmentioning
confidence: 99%
“…Rhino-orbital-cerebral mucormycosis (ROCM) is involved in 50% of the infections, 18% infections are cutaneous, pulmonary mucormycosis contributes to 8% of the cases, 4% cases are related with gastrointestinal mucormycosis, disseminated infections are usually 3%, while 2% are renal infections (Jeong et al, n.d.; Prakash and Chakrabarti, 2021 ). Breast ( Kataria et al, 2016 ), ear ( Prakash et al, 2019 ), spine ( Hadgaonkar et al, 2015 , Shah and Nene, 2017 ), heart ( Bharadwaj et al, 2017 , Krishnappa et al, 2019 ), and bone infections ( Bhatt et al, 2018 , Urs et al, 2016 ) are some of the other less frequent sites of infection reported in India ( Prakash and Chakrabarti, 2021 ).
Fig.
…”
Section: Clinical Forms Of Black Fungusmentioning
confidence: 99%
“…Depending upon the site of involvement, clinically Mucormycosis is classified as rhinoorbital-cerebral (ROCM), pulmonary, gastrointestinal, cutaneous, disseminated Mucormycosis and othersinclude renal, osteomyelitis, endocarditis, peritonitis, ear, breast, uterus, urinary bladder, lymph nodes (16,17). In India, ROCM is the most common type, followed by the pulmonary and cutaneous types (18).…”
Section: Clinical Featuresmentioning
confidence: 99%